Boosting executive skills in the classroom : a practical guide for educators - Cooper-Kahn, Joyce; Foster, Margaret, 1955- (Jossey-Bass, a Wiley Imprint, 2013)
"A guide for helping students with weak Executive Function skills to learn efficiently and effectively Students with weak Executive Function skills need strong support and specific strategies to help them learn in an efficient manner, demonstrate what they know, and manage the daily demands of school. This book shows teachers how to do exactly that, while also managing the ebb and flow of their broader classroom needs. From the author of the bestselling parenting book Late, Lost, and Unprepared, comes a compilation of the most practical tools and strategies, designed to be equally useful for children with EF problems as well as all other students in the general education classroom.Rooted in solid research and classroom-tested experience, the book is organized to help teachers negotiate the very fluid challenges they face every day; educators will find strategies that improve their classroom "flow" and reduce the stress of struggling to teach students with EF weaknesses. Includes proven strategies for teachers who must address the needs of students with Executive Function deficits Contains information from noted experts Joyce Cooper-Kahn, a child psychologist and Margaret Foster, an educator and learning specialist Offers ways to extend learning and support strategies beyond the classroom The book's reproducible forms and handouts are available for free download This important book offers teachers specific strategies to help students with EF deficits learn in an efficient manner, demonstrate what they know, and manage the daily demands of school"--Resumé vydavatele
Keywords: děti s mentálním postižením; vzdělávání; speciální vzdělávací potřeby; výkonová motivace; neuropsychologie; kognitivní procesy; children with mental disabilities; education; special educational needs; achievement motivation; neuropsychology; cognitive processes; příručky; handbooks and manuals